IMPLEMENTASI PROYEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) DALAM MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA SISWA SMP SUNAN GIRI MALANG - Maria Inna; Debora Rambu Newa; Rudy Setiawan; Muhammad Yusi Kamhar (Inteligensi : Jurnal Ilmu Pendidikan, 2023)
The implementation of the Independent Curriculum (Kurikulum Merdeka) through the Project for Strengthening the Profile of Pancasila Students (P5) aims to bolster both student character and competence. This study aims to describe the implementation of P5 at SMP Sunan Giri Malang and analyze its contribution to students' mathematics learning motivation. Employing a qualitative approach with a descriptive case study design, data were collected through observation, in-depth interviews, and documentation. The results indicate that the P5 implementation under the "Entrepreneurship" theme successfully integrated numeracy concepts, such as social arithmetic, into real project activities. The findings reveal a significant increase in students' intrinsic motivation as they understood the practical relevance of mathematics in daily life. Furthermore, the collaborative approach in P5 effectively reduced math anxiety. The teacher's role as a humble and sincere facilitator was a key supporting factor in this success. In conclusion, P5 is not merely a tool for character building but also serves as an effective catalyst for enhancing academic motivation and numeracy literacy for junior high school students in the era of educational transformation.